Effect of Different Protein Levels for Growth of Juaro (Pangasius polyuranodon) Using Resirculation System - Ika Sefriani; Mulyadi '; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from 1 May to 26 July 2015 held at UPT Hatchery in order to find the best fish meal with protein content to support life and growth of Panagsius polyuranodon reared in a recirculation system. The method used in this research is experiment by using completely randomized design (CRD) 1 factor, 3 level treatments and 3 replications. The best result was achieved by protein 37,41% protein level with an average of 6.81 g of absolute growth, the average specific growth rate of 1.13 % respectively, the average feed efficiency of 48.53% and survival by 77.78% , The value of water quality at P3 is temperature: 26,8-30 0C, pH: 6.2 to 6.6 DO: 4.7 to 5.4 mg/L and Amonia: 0.0013 mg/L.Key Words: different protein, Growth rate, pangasidae, Pangasius polyuranodon